Teaching Oral English In Indonesian EFL Contexts During Globalized Challenging Time - Amirullah Abduh; Rosmaladewi Rosmaladewi; Murni Mahmud (Makassar State University, 2021)
Abstract. This paper addresses the limited studies on Oral English (OE) worldwide and the absence of OE research publications from Indonesian contexts. This study aims to fill this knowledge gap. This 6-month research project was undertaken in the Department of English Education at one of the public universities in Makassar, Indonesia. Out of 100 students, 30 student participants and 3 lecturers consented to engage voluntarily in the project. The data from questionnaires were analyzed via Ms. Excel's quantitative analysis thematically. The study indicates that students’ reflections on strategies of teaching OE: appropriate topic for presentation, logical sequence of presented information, and acknowledge the source of teaching materials. This study has the implication for the teaching of OE in other similar geographical contexts and settings and can be useful strategies for OE teachers and practitioners.Keywords: Perceptions, Students, Strategies, Teaching Oral English, EFL